A cookie forming machine. - Shamsuddin, Rosnah (2010)

(untitled)
The present invention relates to a cookie forming machine which is designed to produce the Koye Kacang biscuit or the like. Koye Kacang or Putu Kacang biscuit is a mixture of green bean, sugar and some water. This machine is simple, practical, more hygiene, save cost of production and labor energy. The machine is developed to overcome the labor cost and efficiency problems encountered by Koye Kacang producer. The main components of the machine are feeder tank, horizontal guide plate, pneumatic compressor, presser plate, moulding plate, side plate, connecting steel, conveyor belt, sliding plate and collecting tank. This machine showed 100% efficiency in feeding process at full capacity. Based on the high performance of the machine, it certainly capable to assist Koye Kacang producer to reduce the labor cost and time of processing, thus increasing the productivity considerably.